Extraction and Titration of Leukotoxins from Fusobacterium necrophorum Isolates Recovered from Bovine Liver Abscesses in Sulaimaniyah Region: Suha Ali Hussein1 and Essam F. Al-Jumaily2 - Barhoom, Salameh sh.; Hussein, Suha Ali (The Iraqi Journal of Veterinary Medicine, 2012)
This study was conducted to extract and titrate the leukotoxin of Fusobacteriumnecrophorum isolates recovered from 75abscesses found in 24 livers of slaughtered cattle inSulaimaniyah region. The culture supernatants of these isolates were subjected to thetetrazolium dye reduction test which revealed that the leukotoxin titer values of 34 F.necrophorum subsp. necrophorum isolates ranged from 128 to 1024 (with a leukotoxin titermean of 516±46), whereas the leukotoxin titer values of the 11 F. necrophorum subsp.funduliforme isolates ranged from 0 to 128 (with a leukotoxin titer mean of 73±12).